Effects of dexmedetomidine on pulse pressure variation changes induced by hemorrhage followed by volume replacement in isoflurane-anesthetized dogs - Diniz, Miriely S. [UNESP]; Teixeira-Neto, Francisco J. [UNESP]; Candido, Thaisa D. [UNESP]; Zanuzzo, Felipe S. [UNESP]; Teixeira, Livia R. [UNESP]; Klein, Adriana V.; Nascimento, Paulo do [UNESP] (Wiley-Blackwell, 2014)
ObjectivesTo evaluate the effects of dexmedetomidine (DEX) on changes in pulse pressure variation (PPV) induced by hemorrhage followed by volume replacement (VR) during isoflurane (ISO) anesthesia.DesignProspective, randomized, crossover study.SettingResearch laboratory at a veterinary teaching hospital.AnimalsEight adult dogs.InterventionsAnesthesia was maintained with 1.3 times the minimum alveolar concentration (MAC) of ISO alone or ISO with DEX (ISO-DEX, 1.6 g/kg [bolus], followed by 2 g/kg/h). Atropine was administered 30 minutes prior to hemorrhage in the ISO-DEX treatment. Ventilation was controlled (tidal volume of 12 mL/kg, positive end-expiratory pressure of 7 cm H2O, respiratory rate of 16-20/min) under neuromuscular blockade. After recording baseline data, progressive withdrawal of 10%, 20%, and 30% of blood volume (HV10, HV20, and HV30, respectively [measurements during hemorrhage, indicating x% of blood volume removed]) was followed by VR with autologous blood.Measurements and Main ResultsIn 4 of 8 ISO dogs, hemorrhage decreased mean arterial pressure (MAP) < 60 mm Hg. Based on mean arterial pressure after hemorrhage, dogs were assigned to hypotensive (HG) and normotensive (NG) groups post hoc. During ISO, stroke index and cardiac index decreased with hemorrhage (P < 0.05), while VR normalized or increased these variables. The PPV (%, mean [range]) was increased by hemorrhage from 7 (5-9) to 20 (12-27) and 27 (17-40) at HV20 and HV30, respectively, only in ISO dogs in the HG; PPV returned to baseline after VR. Dexmedetomidine caused increases in systemic vascular resistance (in dogs in HG and NG), and prevented the increase in PPV with hemorrhage.ConclusionsDuring ISO anesthesia, PPV increases in individuals prone to developing hypotension from hypovolemia. Because DEX prevents the increase in PPV associated with hypovolemia, PPV should not be used to guide VR in dogs that have been given DEX.
Keywords: alpha-2 agonist; Frank-Starling; hypovolemia; resuscitation